2004
DOI: 10.17221/3790-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Orchard performance of new plum cultivars on two rootstocks in a trial at Holovousy in 1998-2003

Abstract: Thirteen plum cultivars on two rootstocks (Myrobalan and Wangenheim Prune seedlings) were studied in a trial established in the spring of 1998 at spacings 5 × 1.5 m. Trees were trained as spindles. Čačanska najbolja was the most vigorous in this trial, followed by Čačanska rana, Herman and Domestic Prune. The weakest tree vigour was observed on Wegierka Dabrowicka, followed by Čačanska rodna and Empress. Čačanska najbolja, Wegierka Dabrowicka and Valor had the highest yield per tree, whereas Čačanska rana had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 6 publications
(4 reference statements)
4
9
0
2
Order By: Relevance
“…Meland (2005) found that OPA was the most vigorous. Similarly, BLU grew vigorously in our trial, but was reported as slow growing in the Czech Republic (Blažek et al 2004). Generally, our data were in a good agreement with results of above authors, although ČLE in our study had low tree growth.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Meland (2005) found that OPA was the most vigorous. Similarly, BLU grew vigorously in our trial, but was reported as slow growing in the Czech Republic (Blažek et al 2004). Generally, our data were in a good agreement with results of above authors, although ČLE in our study had low tree growth.…”
Section: Resultssupporting
confidence: 92%
“…All reminding cultivars could be classified like plums with medium fruit size (Blažek and Pištěková 2009), except ČRA and ČNA. These cultivars could be classified as large fruits cultivars on the basis of summarized results (Blažek et al 2004). Mean FW and its variation recorded in this trial corresponded quite well to data observed in literature (Halapija-Kazija et al 2009).…”
Section: Resultssupporting
confidence: 86%
“…In comparison to the results recorded during the first period of testing (Blažek et al 2004), Sanctus Hubertus grafted onto Myrobalan showed the most vigorous behaviour. Similarly, Bluefree was the medium vigorous at the initial period while it was clearly classified as the least vigorous at the end.…”
Section: Discussionmentioning
confidence: 68%
“…Some preliminary results from this trial that were mainly focused on different aspect of the rootstocks effects, were published (Blažek et al 2004.…”
mentioning
confidence: 99%
“…In fresh prune production regions, including some European countries and parts of North America, the 'Stanley', 'President', and 'Bluefre' are often cultivated (Ramming and Cociu, 1991). In Europe, where breeding of prune cultivars has been actively conducted, various cultivars are grown including domestic breed, imported, and traditionally raised cultivars (Blažek et al, 2004;Bozhkova, 2014;Okie and Ramming, 1999;Rakićević et al, 2008;Šebek, 2013). In Japan, growing areas for 26 prune cultivars have been recorded, most of which are imported (MAFF, 2013).…”
Section: Introductionmentioning
confidence: 99%